Orthoplastics Management of Open Lower Limb Fractures at a Major Trauma Centre: Audit of Adherence to BOAST4 Guidelines - Hester Lacey; Kaneka Bernard; Labib Syed; Evie O'Rourke; Yasmin Calvert-Ford; Joanna Bovis; Enis Guryel; Ian King (JPRAS Open)
Introduction: The British Orthopaedic Association Standards for Trauma and Orthopaedics (BOAST) guide the optimal management of open lower limb fractures. Adherence of the newly established Orthoplastic service at the Major Trauma Centre covering the Southeast of England was audited in relation to these standards. Materials and methods: Audit standards were produced. Data were collected using hospital records and the Trauma Audit and Research Network database. All open lower limb fractures managed between August 2020-August 2022 were included. Data collected included patient and injury demographics, and information related to initial and definitive management. Results: Overall, 133 patients were identified, 70 men and 63 women, with an average age of 58 years. Women had a higher average age (69 years) and ASA grade (71% ASA 3 or higher). Low-energy injuries occurred in 69% of women compared to 78% of high-energy injuries in men (p<0.001). Among them, 108 (81%) were debrided within 24 h. The average time to first debridement was 18.78 h, and 95 (75%) were definitively closed within 72 h, 76 with primary closure, 7 with split-thickness skin graft, 7 with local flap and 36 with free flap. Overall, the post-operative infection rate was 13% with 94% of these fractures definitively closed within 72 h. Conclusion: Most open lower limb fractures occurred in older women with higher ASA grade, from low-energy mechanisms. Most injuries were definitively managed as per the BOAST guidelines, but further efforts are required to improve the adherence to initial debridement targets, including training, appropriate resource allocation and implementation of procedures and proformas to guide injury management and improve documentation.